2017
DOI: 10.4314/afrrev.v11i3.16
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurial Financing on National Output: An Empirical Analysis

Abstract: Due to the magnanimous role of entrepreneurial finance in spurring output thereby fostering economic performance as supported by the intermediation and entrepreneurial financing theory, this study explored the influx of entrepreneurial financing on output generation in Nigeria utilizing secondary sourced data over the period of 1992 to 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Also, Ifionu and Akinpelumi (2017) employed OLS method of estimation to ascertain the influence of credit facilities on the nature of long run relationship prevailing between entrepreneurial financing and national output performance in Nigeria. The results revealed that credit facilities played insignificant role to enhance the level of performance in national output.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Also, Ifionu and Akinpelumi (2017) employed OLS method of estimation to ascertain the influence of credit facilities on the nature of long run relationship prevailing between entrepreneurial financing and national output performance in Nigeria. The results revealed that credit facilities played insignificant role to enhance the level of performance in national output.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The present study is underpinned by the Resource-Based Theory of entrepreneurship. This is attributed to the fact that entrepreneurs are hungry for financial resources to stimulate growth (Ifionu & Akinpelumi, 2017). The underlying idea is that a competitive advantage emanates from the effective utilization of tangible and intangible resources.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The challenges impeding on Nigerian entrepreneurs, in an attempt to reduce the financial institution risk perception index of small-scale firms was reviewed by (Ifionu and Akinpelumi, 2017;as cited in Regina et al, 2012). Survey technique was utilized, and measurable investigations revealed that risk appraisal by financers corresponded with the financial records and fund appropriation of small business operators as well as the saving culture of small businesses and how much credit they are willing to give.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…It was also discovered that access to credit for small firms is influenced by previous turnover, current resource base, the age of the firm and execution goals. Ifionu and Akinpelumi (2017) also reviewed the challenges facing entrepreneurship development in Nigeria as evaluated by (Ofili, 2014). The qualitative research methodology was used, and it was discovered that government policies are not such that promote the growth of SME's.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation